Key factors associated with oral health-related quality of life in Sri Lankan adolescents: a cross sectional study - Uttara Amilani; Prasanna Jayasekara; Hannah E. Carter; Sameera Senanayake; Sanjeewa Kularatna (BMC, 2021)
Abstract Background Oral Health Related Quality of Life (OHRQoL) measures have emerged as an important oral health outcome that is able to reveal the subjective burden of illness due to oral diseases. The association between sociodemographic and socioeconomic factors, clinical dental conditions and OHRQoL indicators has been investigated in adolescent populations across the world. The purpose of this study was to investigate key factors associated with oral health-related quality of life of Sri Lankan adolescents. Methods A cross sectional study was conducted in a sample of 15-19 year-old secondary school students in the Gampaha district of Sri Lanka. The data was collected using two self-administered questionnaires. A modified Sinhalese version of the Oral Impact on Daily Performance (OIDP) questionnaire that has been validated for Sri Lankan adolescents was administered. A second questionnaire collected information on socioeconomic characteristics, oral health care seeking and oral health behaviours. A clinical oral examination was performed on each participant. Oral health related quality of life was measured using OIDP domains and total OIDP scores. Poisson regression was used to investigate the key factors associated with the OIDP additive score. Results A total of 1332 adolescents participated in the study. Negative quality of life impacts were more prevalent in the social and psychological domains of OIDP as compared with the functional domain. Total OIDP scores ranged from 0 to 36 with a mean of 3.16 (SD = 4.71). The multivariable analysis revealed that increasing age, low income, brushing teeth only once per day, and increased number of decayed teeth were found to be associated with poor overall OHRQoL, while male gender, frequent oral healthcare seeking patterns and absent dento-facial anomalies were associated with good OHRQoL. Conclusion This study identified modifiable behavioural and oral health related factors which are associated with OHRQoL in Sri Lankan adolescents. Oral health interventions should target these modifiable factors to improve the OHRQoL in these populations.